2013
DOI: 10.1103/physrevlett.111.057005
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Superconducting State of Monolayer Pb Films Grown on GaAs(110) in a Strong Parallel Magnetic Field

Abstract: Two-dimensional (2D) superconductivity was studied by magnetotransport measurements on single-atomic-layer Pb films on a cleaved GaAs(110) surface. The superconducting transition temperature shows only a weak dependence on the parallel magnetic field up to 14 T, which is higher than the Pauli paramagnetic limit. Furthermore, the perpendicular-magnetic-field dependence of the sheet resistance is almost independent of the presence of the parallel field component. These results are explained in terms of an inhomo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 28 publications
8
78
1
Order By: Relevance
“…It is shown that the critical field oscillates as a function of the nanofilm thickness which is explained in terms of the electron energy quantization induced by the confinement in the direction perpendicular to the film. It is found that the zero-temperature critical field in the nanofilms tends to be higher than the ClogstonChandrasekhar paramagnetic limit which is in agreement with recent experiments [15]. The validity of the CC formula can be restored by the use of the thickness-dependent energy gap.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It is shown that the critical field oscillates as a function of the nanofilm thickness which is explained in terms of the electron energy quantization induced by the confinement in the direction perpendicular to the film. It is found that the zero-temperature critical field in the nanofilms tends to be higher than the ClogstonChandrasekhar paramagnetic limit which is in agreement with recent experiments [15]. The validity of the CC formula can be restored by the use of the thickness-dependent energy gap.…”
Section: Discussionsupporting
confidence: 74%
“…Such observation for the Pb nanofilms has been recently reported in Ref. [15] in which the experimentally measured critical field H C,|| has been much higher than the paramagnetic limit H CC . The discrepancy of the calculated critical field and H CC results from the deviation of the energy gapΔ from its bulk value.…”
Section: Resultsmentioning
confidence: 72%
“…14, R N is lower and T c0 is higher for Pb and Bi. 10) We attribute this to the atomically flat surface of the cleaved GaAs substrate. Films of In and Pb show superconductivity even in the monolayer regime (d 0.3 nm).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…10) We used a nondoped insulating GaAs single-crystal substrate so as not to create conduction channels in the substrate. Current and voltage electrodes were prepared at room temperature by the deposition of gold films onto noncleaved surfaces.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation